Analisis Faktor Yang Memengaruhi Repurchase Intention Pada Konsumen Toko Kopi Klasik Islamic Village - Ninuk Yasmarini; Adryan Rachman (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The rapid development of the coffee industry in Indonesia has led to the emergence of various coffee shops with unique concepts, one of which is Toko Kopi Klasik. This study aims to analyze the influence of Service Quality, Store Atmosphere, and Social Media Marketing on Repurchase Intention with eWOM as a mediating variable. The research uses a survey method involving 120 respondents who are consumers of Toko Kopi Klasik. Data were analyzed using the PLS-SEM method with the help of SmartPLS 3.0 software. The results show that Store Atmosphere, Social Media Marketing, and eWOM have a positive and significant impact on Repurchase Intention, while Service Quality does not have a significant impact. Additionally, Store Atmosphere and Social Media Marketing are also found to have a positive and significant impact on eWOM. These findings imply the importance of managing store ambiance, social media, and online reviews to enhance consumer repurchase intention.